2015
DOI: 10.1186/s40880-015-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b5 reductase 2 suppresses tumor formation in nasopharyngeal carcinoma by attenuating angiogenesis

Abstract: BackgroundCytochrome b5 reductase 2 (CYB5R2) is a potential tumor suppressor that inhibits cell proliferation and motility in nasopharyngeal carcinoma (NPC). Inactivation of CYB5R2 is associated with lymph node metastasis in NPC. This study aimed to explore the mechanisms contributing to the anti-neoplastic effects of CYB5R2.MethodsPolymerase chain reaction (PCR) assays were used to analyze the transcription of 84 genes known to be involved in representative cancer pathways in the NPC cell line HONE1. NPC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…CYB5R2 has been identified as a tumor suppressor that is epigenetically regulated 46 . CYB5R2 negatively regulates vascular endothelial growth factor 47 which could contribute to its tumor suppressor activity. Furthermore, CYB5R2 is epigenetically regulated through promoter methylation 48 , associated with patient survival of glioblastoma, and functions in collagen maturation, immunoregulation via toll-like receptor pathways, and osmotic stress 49 .…”
Section: Discussionmentioning
confidence: 99%
“…CYB5R2 has been identified as a tumor suppressor that is epigenetically regulated 46 . CYB5R2 negatively regulates vascular endothelial growth factor 47 which could contribute to its tumor suppressor activity. Furthermore, CYB5R2 is epigenetically regulated through promoter methylation 48 , associated with patient survival of glioblastoma, and functions in collagen maturation, immunoregulation via toll-like receptor pathways, and osmotic stress 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CYB5R2 is under expressed in human DR [ 18 ]. In addition, Ming et al [ 17 ] found that CYB5R2 is involved in the regulation of angiogenesis. In this study, CYB5R2 was also shown to be downregulated in the serum of patients with DR. Functionally, the knockdown of CYB5R2 promoted proliferation, migration, and angiogenesis, while inhibited apoptosis of hRMECs.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is an important angiogenic factor in DR, and new evidence suggests that the VEGF antibody treatment may be a new therapy for DR [ 42 , 43 ]. Multiple analyses have also shown that both MEG3 and CYB5R2 have a regulatory effect on VEGF [ 12 , 17 ]. Therefore, future studies will focus on the role of VEGF in DR mediated by MEG3/miR-6720-5p/CYB5R2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information on the role of CYB5R in carcinogenesis is extremely poor and contradictory. The study [30] [31] demonstrate that CYB5R2 has an oncosuppressive effect due to the suppression of neoangiogenesis. Contrary data was obtained by the authors of [10], who proved the key role of CYB5R3 in extravasation and colonization of cancer cells after intravenous administration to mice.…”
Section: Discussionmentioning
confidence: 99%